2018
DOI: 10.1007/s12185-018-2442-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of post-transplant mucosal-associated invariant T cell recovery on the development of acute graft-versus-host disease in allogeneic bone marrow transplantation

Abstract: Mucosal-associated invariant T (MAIT) and invariant natural killer T (iNKT) cells are T cell subpopulations that possess innate-like properties. We examined the impact of post-hematopoietic stem cell transplantation (HSCT) MAIT and iNKT cell recovery on the clinical outcomes of 69 patients who underwent allogeneic HSCT at Kyoto University Hospital. Multivariate analyses identified the absolute number of MAIT cells (< 0.48/μL on day 60 post-HSCT) as the sole independent risk factor for grade I-IV and grade II-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…High frequencies of tumour-infiltrating MAIT cells are associated with poor clinical outcomes for patients with HCC. In contrast, in the context of haematological malignancies, a higher frequency of MAIT cells after allogeneic haematopoietic cell transplantation is associated with less graft-versus-host disease (GVHD) 140,141 . Mouse studies have also shown a beneficial role of MAIT cells against GVHD and highlighted their role in maintaining gut integrity 142 .…”
Section: Mait Cells In Human Cancersmentioning
confidence: 99%
“…High frequencies of tumour-infiltrating MAIT cells are associated with poor clinical outcomes for patients with HCC. In contrast, in the context of haematological malignancies, a higher frequency of MAIT cells after allogeneic haematopoietic cell transplantation is associated with less graft-versus-host disease (GVHD) 140,141 . Mouse studies have also shown a beneficial role of MAIT cells against GVHD and highlighted their role in maintaining gut integrity 142 .…”
Section: Mait Cells In Human Cancersmentioning
confidence: 99%
“…In the allo-HCT setting, no associations between high MAIT cell numbers and protection from infections have been reported so far [93]. However, low frequencies of MAIT cells in the graft and post-HCT are associated with severe GvHD [74,[92][93][94][95], and higher numbers seem to be associated with improved overall survival [94].…”
Section: Mait Cellsmentioning
confidence: 99%
“…Reconstitution of MAIT cells post-HCT significantly correlates with age [92,94] and cell source [92,93,96,97]. Early MAIT cell reconstitution is driven by the HPE of the MAIT cells transferred with the graft [93].…”
Section: Mait Cellsmentioning
confidence: 99%
“…pDCs are known to promote tolerance via Treg expansion, 19 whereas MAIT cells enhance gastrointestinal tract barrier function and microbiome diversity and inhibit alloantigen presentation after SCT. 20,21 To our knowledge, neither population has been linked to GVL effects previously. It is possible that temporal modulation of these innate cell populations can modify leukemia and alloantigen presentation in a way that favors GVL over GVHD.…”
Section: Discussionmentioning
confidence: 89%